Health in All Policies as a Strategic Policy Response to NCDs - Lin, Vivian; Jones, Catherine; Wang, Shiyong; Baris, Enis (World Bank, Washington, DC, 2014)
The aim of Health in All Policies (HiAP) is to bring diverse sectors together to find shared solutions; it focuses on identifying 'win-win' or 'cobenefits' such that policy measures contribute not only to improved health outcomes but also to outcomes desired by other sectors, such as education, environment, welfare, agriculture, and transportation. HiAP can be applied to NCD prevention and control from three different entry points: risk factors or conditions, population groups (including life course), and sectors. (HiAP) is a relatively new concept and policy practice that attempts to incorporate consideration into the policy decision-making process of how public policies and programs affect community health and well-being. It represents a way of working across sectors that aim to find solutions for complex, interrelated, and persistent problems. With the global epidemic in non-communicable diseases (NCDs), HiAP offers a potential approach and a pathway to secure coordinated action on social determinants of health that relate to NCDs and result in health inequalities. Promising examples can be seen globally for action on both specific NCD risk factors as well as in a more systemic approach to policy decision making.